Effectiveness of the Prof. Tito Storybook in Enhancing Student Learning in Indonesian Language and Natural Science for Fifth Grade Elementary School Students - Azima, Nana Fauzana; Iraqi, Hana Shilfia; Algifari, Arif; Zahra, Lailatul; Putri, Ellsy Rahmadani (Universitas Pendidikan Indonesia, 2024)
This research addresses the issue of unsuitable children's storybooks influencing elementary students' thinking patterns by mirroring adult behaviors, prompting the development of the modern children's storybook